Case report: Multiple approach analysis in a case of clinically assessed myotonia congenita - Lucchiari, Sabrina; Fortunato, Francesco; Meola, Giovanni; Mignarri, Andrea; Pagliarani, Serena; Corti, Stefania; Comi, Giacomo P.; Ronchi, Dario (Frontiers in Genetics, 2024)
Myotonia congenita, both in a dominant (Thomsen disease) and recessive form (Becker disease), is caused by molecular defects in CLCN1 that encodes the major skeletal muscle chloride channel, ClC-1. This channel is important for the normal repolarization of muscle action potentials and consequent relaxation of the muscle, and its dysfunction leads to impaired muscle relaxation after voluntary or evoked contraction and muscle stiffness. More than 300 CLCN1 pathogenic variants have been found in association with congenital myotonia, inherited as recessive or dominant traits (with complete or incomplete penetrance). In this study, we describe the case of a 44-year-old woman complaining of “leg stiffness” since the age of 20 years and presenting with transient muscle weakness, especially after sitting for several minutes, with grip myotonia and feet myotonia, cold-sensitive and warm-up. The strength was normal, but muscle hypertrophy in the lower limbs was evident. EMG myotonia was detected in all explored muscles. The patient’s father had precocious cataract correction but did not show myotonic discharges at EMG. Examination of the patient’s sons (aged 18 years and 12 years) was unremarkable. The patient started treatment with mexiletine, with improvement in grip myotonia and limb stiffness, but it was soon interrupted due to gastrointestinal disturbances. Direct sequencing of CLCN1 identified the previously described heterozygous intronic variant c.1471 + 1G > A, which resulted in the skipping of exon 13 in the CLCN1 muscle transcript. In addition, the rare heterozygous synonymous nucleotide change c.762C > T p.Cys254Cys was identified and predicted to alter physiological splicing. The detection of multiple splicing abnormalities leading to premature termination codons supported the in silico prediction. We developed a Western blot assay to assess the ClC-1 protein in muscle biopsy, and we observed that ClC-1 levels were consistently reduced in the patient’s muscle, supporting the pathogenic behavior of the variants disclosed. Overall, we report a novel case of Becker myotonia and highlight the importance of multiple levels of analysis to achieve a firm molecular diagnosis.